Philippine medical thesaurus on psychiatry and psychology psychological phenomena and process in Tagalog - Bautista, Vanessa M. (2005)
This research produced an additional Philippine Medical Thesaurus on Psychiatry and Psychology in Tagalog. This time concentrating on FO2 facet-Psychological Phenomena and Processes. Using the top-down or "deductive" approach and concept of "Domain Analysis" as frameworks, data were obtained from the Medical Subject Headings (MeSH) 2005, from translation tools such as dictionaries and glossaries ranked by a linguist, and from psychiatrists, guidance counselors, and professors as respondents.